KOMUNIKASI KELUARGA DALAM MENANGKAL PORNOMEDIA PADA ANAK - Musfiah Saidah (MediaTor (Jurnal Komunikasi), 2022)
Currently exposure to pornography in children threatens from various sides, ranging from relationships to the media. The threat of pornography in various media is a reminder for families to be able to pay special attention to children. Meanwhile, in essence, children are a representation of demographic growth that will help create national resilience. This is where the role of the family is needed in protecting and educating. The research used a qualitative approach with a phenomenology method with the collecting data by interview and get the additional source from news in newspaper. The subject of this research is communication in family and the object is pornographic content. The results of this study aim to show the importance of building family communication in order to ward off the onslaught of pornography on children. Effective family communication based on Islamic values is effective as an antidote to even the most widespread information epidemics, such as the epidemic of negative pornography on children. Based on this research, the author initiated a communication pattern in the family, which can be divided into three stages, namely in the form of directions, actions, and invitations. It is hoped that in the future there will be an effective communication pattern between children and parents based on Islamic values.